The phenomenon of bullying between past and present in the light of the Holy Quran - Osman Al Shahd, Aml Abdullah (Journal of Islamic Sciences, 2021)
This study aimed at prove that bullying is an ancient term, besides shedding light on prophets (peace be upon them) that have been bullied by their people and how they dealt with bullies among their people in order to spread their religious message. The study examined the inductive analytical method to describe bullying phenomena throw the Quran verses. The study concluded that there were negative and dangerous effects on the victims, but the prophets had protected because they were strong and patient enough.